2003
DOI: 10.1359/jbmr.2003.18.7.1308
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Determinants of Femoral Strength in Growth Hormone-Deficient Transgenic Growth-Retarded (Tgr) Rats

Abstract: The extent to which childhood GHD affects adult fracture risk is unclear. We measured femoral strength in adult transgenic growth-retarded rats as a model of GHD. Long-term, moderate GHD was accompanied by endocrine and morphometric changes consistent with a significant reduction in femoral strength.Introduction: Childhood growth hormone deficiency (GHD) is associated with osteopenia, but little is known about its effects on subsequent adult bone strength and fracture risk. Materials and Methods:We have theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 48 publications
3
16
1
Order By: Relevance
“…This obese phenotype, which is observed in childhood onset GH deficiency (Growth Hormone Research Society 2000, Raine et al 2006), is also present in the Tgr rat (Evans et al 2003, Davies et al 2007), but we have shown that the more profoundly GH-deficient dw/dw rat is surprisingly lean and hypoleptinaemic (Davies et al 2007). This difference is potentially significant, since low levels of circulating leptin are associated with prevention of bone loss (Martin et al 2007), and high leptin and extreme obesity are accompanied by decreased bone formation (Martin et al 2007, Núñez et al 2007.…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…This obese phenotype, which is observed in childhood onset GH deficiency (Growth Hormone Research Society 2000, Raine et al 2006), is also present in the Tgr rat (Evans et al 2003, Davies et al 2007), but we have shown that the more profoundly GH-deficient dw/dw rat is surprisingly lean and hypoleptinaemic (Davies et al 2007). This difference is potentially significant, since low levels of circulating leptin are associated with prevention of bone loss (Martin et al 2007), and high leptin and extreme obesity are accompanied by decreased bone formation (Martin et al 2007, Núñez et al 2007.…”
Section: Introductionsupporting
confidence: 51%
“…SD rats used in study 3 were purchased from Charles River (Margate, UK) and maintained under the same conditions in the School of Biosciences, Cardiff University. Rats were permitted ad libitum access to food and water, standard chow animals used in these studies was calculated from our previously published endocrine and metabolic studies (Evans et al 2003, Thompson et al 2004, Davies et al 2007) using the Lenth's Power and Sample Size software (Lenth RV (2006) Java Applets for Power and Sample Size (Computer software), retrieved 20/02/2003 from http://www.stat.uiowa.edu/wrlenth/Power), with the power set at O75% and assuming S.D.s of 32 and 36% for two-group t-test and one-way ANOVA four-group comparisons respectively. Study 1: transpubertal development of trabecular organisation in Tgr and dw/dw rats Groups of non-fasting 3-, 6-, 9-and 52-week-old male wt, Tgr and dw/dw rats (nZ3-6) from the Cardiff colonies were weighed, anaesthetised with halothane and killed by decapitation.…”
Section: Gh-deficient Ratsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Thus, scientific effort focuses on the analysis of bony healing processes in large defects and on possibilities to reduce the healing time using a variety of techniques (e.g., growth factors and stem cells). [4][5][6][7][8] A major drawback of experimental studies is the lack of stable intramedullary fracture fixation, especially in small animals. 9,10 Single K-wire stabilization is widely used for fracture care in small animals.…”
Section: Introductionmentioning
confidence: 99%